2021
DOI: 10.3390/app11199256
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Silica–MWCNTs/PDMS Composite Coatings Deposited on Plasma Activated Glass Supports

Abstract: In this paper, we focus on fabrication and physicochemical properties investigations of silica–multiwalled carbon nanotubes/poly(dimethylsiloxane) composite coatings deposited on the glass supports activated by cold plasma. Air or argon was used as the carrier gas in the plasma process. Multiwalled carbon nanotubes were modified with poly(dimethylsiloxane) in order to impart their hydrophobicity. The silica–multiwalled carbon nanotubes/poly(dimethylsiloxane) nanocomposite was synthesized using the sol–gel tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Contributions to this Special Issue focus on different aspects of Atmospheric-Pressure Plasma Technology, giving valuable examples of applied research in the field. This Special Issue of Applied Sciences, "Recent Advances in Atmospheric-Pressure Plasma Technology", includes one review [3] and eight original papers [4][5][6][7][8][9][10][11], providing new insights into the application of atmospheric pressure plasma technology. Domonkos et al [3] discussed the application of cold atmospheric pressure plasma (CAPP) technology in different configurations.…”
Section: Review Of Special Issue Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributions to this Special Issue focus on different aspects of Atmospheric-Pressure Plasma Technology, giving valuable examples of applied research in the field. This Special Issue of Applied Sciences, "Recent Advances in Atmospheric-Pressure Plasma Technology", includes one review [3] and eight original papers [4][5][6][7][8][9][10][11], providing new insights into the application of atmospheric pressure plasma technology. Domonkos et al [3] discussed the application of cold atmospheric pressure plasma (CAPP) technology in different configurations.…”
Section: Review Of Special Issue Contentsmentioning
confidence: 99%
“…Chodkowski et al [5] focused on fabrication and physicochemical properties investigations of silica-multiwalled carbon nanotubes/poly(dimethylsiloxane) composite coatings deposited on the glass supports activated by cold plasma in air or argon. They found that the type of plasma influences the surface properties of the deposited coating.…”
Section: Review Of Special Issue Contentsmentioning
confidence: 99%
“…Therefore, it can be expected that polymer materials doped with carbon nanoparticles will find application in medicine and biology as drugs, antimicrobial agents [16,17], and inhibitors (catalysts) of enzymatic processes. An important area of application of fullerene composites in a polymer matrix is the development of biological sensors [18][19][20] and bacterial biosensors [16,21,22] based on the electrically conductive and corrosive properties of fullerenes [23,24].…”
Section: Introductionmentioning
confidence: 99%